Mechanisms, Transmissions and Applications Proceedings of the Fourth MeTrApp Conference 2017 - Dede, Mehmet Ismet Can.; İtik, Mehmet; Lovasz, Erwin-Christian.; Kiper, Gökhan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume contains the proceedings of MeTrApp 2017, the 4th Conference on Mechanisms, Transmissions and Applications, that was held in Trabzon, Turkey, July 3-5, 2017. The topics treated in this volume are Mechanism Design, Parallel Manipulators, Control Applications, Mechanical Transmissions, Cam Mechanisms, and Dynamics of Machinery. The conference was organised by the IFToMM Technical Committees for "Linkages and Mechanical Controls" and "Gearing and Transmissions" under the patronage of the IFToMM and sponsorship of Karadeniz Technical University, Izmir Institute of Technology and IFToMM Turkey (MAKTED). The aim of the conference was to bring together researchers, scientists, industry experts and students to provide, in a friendly and stimulating environment, the opportunity to exchange know-how and promote collaboration in the field of Mechanism and Machine Science. .
Preface -- Part I: Mechanism Design -- Morphing Wings and Control Surfaces: A New Approach in Aircraft Design, by Yavuz Yaman -- Designing Human Powered Balers For Straw Bale Construction in Developing Countries: The Case of Haiti, by Carlo Ferraresi, Walter Franco, Giuseppe Quaglia -- Guiding linkages with remote centre of rotation for thermal cutting processes, by Carsten Teichgräber, Jörg Müglitz, Maik Berger -- Structural Synthesis of 2R1T Type Mechanisms for Minimally Invasive Surgery Applications, by Abdullah Yasır, Gökhan Kiper -- 3R1H Pseudo-Rigid-Body Model for Compliant Mechanisms with Inflection Beams, by Yue-Qing Yu, Shun-Kun Zhu -- A Spatial Four-bar Linkage RSPS for Ball-bar to Test R-pair, by Delun Wang, Zhi Wang, Xiaopeng Li, Huimin Dong, Shudong Yu -- Leg Mechanisms Motion Characteristics, by Adriana Comanescu -- Design and Dimensional Optimization of a Novel Walking Mechanism with Firefly Algorithm, by Özgün Selvi, Samet Yavuz -- Part II: Cam Mechanisms -- Improving the kinematics of motion curves for cam mechanisms using NURBS, by Thi Thanh Nga Nguyen, Stefan Kurtenbach, Mathias Hüsing, Burkhard Corves -- Assessment of the Rolling Contact Fatigue, by Monika Hejnova -- The Stress Distribution in the Contact Region of a Cam Mechanism General Kinematic Pair, by Jirí Ondrášek -- Part III: Parallel Manipulators -- 5 DoF Haptic Exoskeleton for Space Telerobotics - Shoulder Module, by Dan Teodor Margineanu, Erwin-Christian Lovasz, Gruescu Corina, Valentin Ciupe, Santra Tatar -- Kinematic design of a tripod parallel mechanism for robotic legs, by Matteo Russo, Marco Ceccarelli -- Parallel manipulators: practical applications and kinematic design criteria.Towards the modular reconfigurable robots, by Alfonso Hernández Frías, Mónica Urizar, Erik Macho, Victor Petuya -- Two-degree-of-freedom spacial parallel manipulator for laser interferometry-based Tracker, by Baris Celik, Takaaki Oiwa, Kenji Terabayashi, Junichi Aasama -- Part IV: Control Applications -- Design of Artificial Neural Network Predictor for Trajectory Planning of an Experimental 6 DOF Robot Manipulator, by Sahin Yildirim, Burak Ulu -- Fault-Tolerance Experiments with a Kinematically Redundant Holonomic Mobile Robot, by Mehmet Ismet Can Dede, Osman Nuri Sahin, Onur Celik -- Dual-Loop Motion Control for Geometric Errors and Joint Clearances Compensation of a Planar 2PRP-PPR Manipulator, by Santhakumar Mohan, Jayant Kumar Mohanta, Mathias Hüsing, Burkhard Corves -- The Effects of Admittance Term on Back-drivability, by Ogulcan Isitman, Orhan Ayit, Mehmet Ismet Can Dede -- Design and proposed model reference trajectory, by Sahin Yildirim, Kirakoya Abdoulaye Ben-Aziz -- Part V: Mechanical Transmissions -- Free Vibration and Sensitivity Analysis of RV Reducer, by Yuhu Yang, Chuan Chen -- Sensation. Existence of a Gear Variator is Proved, by Konstantin Ivanov -- Parameterized Substructure Model of PGT for Finite Element Contact Analysis, by Huimin Dong, Chu Zhang, Zhang Jili, Delun Wang -- On the Impact of Transmission Error on the Dynamic Behavior of Geared-Linkages, by Domenico Mundo, Shadi Shweiki, Piervincenzo Catera -- Effect of the Coil Shape on Magnetic Field of an Electromagnet for Contactless Power Transmission to Microrobots, by Nail Akçura, Abdulkareem Alasli, Levent Çetin -- Part VI: Dynamics of Machinery -- The Edge of Chaos in Kinematics and Dynamics of Mechanism, by Z.-H. Liu, Jin Xie, Y. Chen -- Dynamics of Orthogonal Mechanism of Vibrating Table in View of Friction, by Zharilkassin Iskakov, Kuatbay Bissembayev, Nutpulla Jamalov -- Design of Neural Network Predictor for Vibration Analysis of a Drill Column Machine During Drilling Plastic Work-Pieces, by Sahin Yildirim, Emir Esim -- Railway Vehicle Model Developed by ASELSAN, by Mustafa Nicem Tanyeri, Murat Gültekin -- Author Index.
Keywords: Machinery; Control engineering; Robotics; Automation; Multibody systems; Vibration; Mechanics, Applied; Machinery and Machine Elements; Control, Robotics, Automation; Multibody Systems and Mechanical Vibrations